2021
DOI: 10.3390/jcm10235684
|View full text |Cite
|
Sign up to set email alerts
|

Post-Contrast Acute Kidney Injury after Acute Stroke—Insights from a German Tertiary Care Center

Abstract: Background: Our aim was to investigate the relationship between additional iodinated contrast medium (CM) application for acute stroke imaging and Post-Contrast Acute Kidney Injury (PC-AKI). Methods: We performed a retrospective analysis of consecutive patients with acute stroke who received a CT angiogram (CTA) with or without additional CT perfusion (CTP) at admission between 2017 and 2020. The primary endpoint was the incidence of PC-AKI. Potential causes of renal function impairment were recorded and logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2 Recent studies have suggested that the use of additional contrast medium to facilitate imaging such as CT perfusion is not associated with increased rates of acute kidney injury (AKI). 3 These recommendations are reflected in departmental protocols. Figure 1 presents the component of the institutional code stroke protocol pertaining to renal function and performing scans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent studies have suggested that the use of additional contrast medium to facilitate imaging such as CT perfusion is not associated with increased rates of acute kidney injury (AKI). 3 These recommendations are reflected in departmental protocols. Figure 1 presents the component of the institutional code stroke protocol pertaining to renal function and performing scans.…”
Section: Introductionmentioning
confidence: 99%
“…contrast 2 . Recent studies have suggested that the use of additional contrast medium to facilitate imaging such as CT perfusion is not associated with increased rates of acute kidney injury (AKI) 3 . These recommendations are reflected in departmental protocols.…”
Section: Introductionmentioning
confidence: 99%